2015
DOI: 10.1038/nbt.3127
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased detection of off-target cleavage by CRISPR-Cas9 and TALENs using integrase-defective lentiviral vectors

Abstract: The utility of CRISPR-Cas9 and TALENs for genome editing may be compromised by their off-target activity. We show that integrase-defective lentiviral vectors (IDLVs) can detect such off-target cleavage with a frequency as low as 1%. In the case of Cas9, we find frequent off-target sites with a one-base bulge or up to 13 mismatches between the single guide RNA (sgRNA) and its genomic target, which refines sgRNA design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
332
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(347 citation statements)
references
References 20 publications
6
332
2
2
Order By: Relevance
“…These nucleases, however, can induce off-target mutations, limiting their utility in research and medicine (Cradick et al 2013;Fu et al 2013;Hsu et al 2013;Pattanayak et al 2013;Cho et al 2014). Recently, we and other groups independently presented several different methods for profiling genome-wide specificities of RGENs, which consist of gRNAs and the Cas9 protein originated from Streptococcus pyogenes, in human cells (Frock et al 2015;Kim et al 2015;Ran et al 2015;Tsai et al 2015;Wang et al 2015). All of these methods rely on high-throughput sequencing of human genomic DNA that is cleaved by RGENs in cells or in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These nucleases, however, can induce off-target mutations, limiting their utility in research and medicine (Cradick et al 2013;Fu et al 2013;Hsu et al 2013;Pattanayak et al 2013;Cho et al 2014). Recently, we and other groups independently presented several different methods for profiling genome-wide specificities of RGENs, which consist of gRNAs and the Cas9 protein originated from Streptococcus pyogenes, in human cells (Frock et al 2015;Kim et al 2015;Ran et al 2015;Tsai et al 2015;Wang et al 2015). All of these methods rely on high-throughput sequencing of human genomic DNA that is cleaved by RGENs in cells or in vitro.…”
mentioning
confidence: 99%
“…High-throughput, genomewide translocation sequencing (HTGTS) is based on translocations induced by nonhomologous end-joining (NHEJ) repair of two concurrent DNA double-strand breaks (DSBs) in cells (Frock et al 2015). Both genome-wide, unbiased identification of DSBs enabled by sequencing (GUIDE-seq) (Tsai et al 2015) and integration-deficient lentiviral vector (IDLV) capture (Wang et al 2015) rely on NHEJ-mediated insertions of small duplex oligonucleotides or lentiviral vectors, respectively, at cleavage sites. Direct in situ breaks labeling, enrichment on streptavidin, and next-generation sequencing (BLESS) is a method of capturing DSBs in fixed cells (Crosetto et al 2013;Ran et al 2015).…”
mentioning
confidence: 99%
“…Our observations are in agreement with previous findings in which IDLVs have been used to detect and map off-target cleavages by CRISPR/Cas9 and TALEN systems. 61 In their study, Wang and colleagues 61 reported that co-delivery of IDLV and CRISPR/Cas9 (delivered as expression plasmids) induced a 2-to 3-fold increase in integration. Furthermore, the 1%-10% off-target indels formation reported in Wang et al 61 is consistent with our observations of mild increase in the overall integration rate of IDLV-CRISPR/Cas9.…”
Section: Discussionmentioning
confidence: 99%
“…61 In their study, Wang and colleagues 61 reported that co-delivery of IDLV and CRISPR/Cas9 (delivered as expression plasmids) induced a 2-to 3-fold increase in integration. Furthermore, the 1%-10% off-target indels formation reported in Wang et al 61 is consistent with our observations of mild increase in the overall integration rate of IDLV-CRISPR/Cas9. Altogether, our results demonstrate that the episomal status of non-integrating vectors is not compromised by CRISPR/Cas9, and that the gene editing reported in Figure 2 arises from transient expression of the episomal vector.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, DNA accessibility and off-target binding are determined ad hoc for every application. Off-target binding is related to flexibility in PAM sequence recognition and permitted mismatches in the PAM-distal part of the sgRNA (Kim et al, 2015;Ran et al, 2015;Tsai et al, 2015;Wang et al, 2015b;Leenay et al, 2016). Efforts to reduce off-target binding include rational redesign of Cas9 for higher PAM specificity (Kleinstiver et al, 2015), reduction of non-specific charge interactions between Cas9 and non-target DNA strand or hydrogen bonding between Cas9 and the backbones of the target DNA strand and the sgRNA (Kleinstiver et al, 2016), as well as use of truncated sgRNAs (Fu et al, 2014).…”
Section: Applications Of the Dcas9 Toolmentioning
confidence: 99%